Trade Shocks, Job Insecurity and Individual Health - Andreea Alexandra Piriu (Global Labor Organization (GLO), 2021)
As the COVID-19 pandemic unfolds, future health care expenditure is likely the discriminant between nations who will build resilience and those who will not. Despite costly labor-market adjustments due to increased international trade over the last two decades, the health effects of trade liberalization are underexplored, with potentially wide implications for public policy and national budgets. Given the remarkable increase in trade volumes between Germany and China following reunification, this paper studies the causal effects of Chinese import competition on the health outcomes of individuals working in the German manufacturing sector. Results in this reduced-form approach exploiting region-industry variation in imports over 22 years show that higher import competition from China increases the individual demand for healthcare and probability of developing chronic illness via job insecurity, job loss and occupational change, an increased reliance on social welfare, and wage reduction. I find that individuals increase their visits to the doctor by 14 per cent and are 18.4 to 20.6 per cent more likely to develop chronic illness, on average. Results are robust for alternative health outcomes and across different population subgroups. The paper calls for reshaping health policy such that it governs well-being, starting with prevention and adequate care for working individuals: amidst globalization and recent chronic disease management, it is fundamental that future sustainable health policy champions the idea that creating better jobs means avoiding preventable costs of care from increased healthcare utilization and hence more effective chronic care through the introduction of preventive primary care plans for vulnerable working population segments.
Keywords: F14; F16; I12; I15; 330; trade; labor; job insecurity; individual health; chronic illness; healthcare utilization